PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI PEMBELAJARAN PEMROGRAMAN DASAR - Prawesti, Asmarita Dela Dwi; Mary, Thomson; kurniawan, haris (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
The implementation of information and computer technology (ICT) in learning media can have a positive impact on students' learning outcomes. ICT in learning media can provide stronger and higher quality learning experiences for students. ICT-based interactive multimedia in learning enables students to be more motivated to learn anytime and anywhere in an enjoyable way. The purpose of this research is (1) to produce valid interactive learning media on basic programming learning material; (2) to determine the response of educators and students to the interactive learning media produced. This type of research uses the Research and Development (R&D) method with the ADDIE development model, which has five stages: Analysis, Design, Development, Implementation, and Evaluation. The population in this study was the tenth-grade students of SMK Negeri 3 Padang. The data analysis technique used validity and practicality tests. Based on the data analysis, the average validation score for the media was 0.93, categorized as